Thermophysical properties and heat transfer performance of Aqueous inhibited propylene glycol/MXene nanofluid for solar photovoltaic/ thermal cooling system - Abd Malek, Norhazwani; Masuri, S. U.; Saidur, R.; Tan, K. H.; Rajamony, Reji Kumar; Supeni, Eris Elianddy; Aiza Jaafar, C. N.; Pandey, A. K. (Springer Science and Business Media B.V., 2025)
The main objective of this research is to explore the thermophysical properties and heat transfer performance of aqueous inhibited propylene glycol/MXene nanofluid for a solar photovoltaic/thermal cooling system. A thorough characterization analysis of the nanofluid was conducted, assessing its morphology, chemical structure, stability, thermal conductivity, viscosity, specific heat capacity, and density. The findings indicate that the addition of MXene nanosheets significantly enhances the thermal conductivity and specific heat capacity while maintaining stability, despite a moderate increase in viscosity and density. The maximum thermal conductivity and specific heat capacity of the nanofluid are around 0.81 Wm−1K−1 and 9.1 kJ kg−1K−1, respectively, at 60 °C and a MXene loading concentration of 0.2 mass%. In comparison with the aqueous IPG, the density increase of the nanofluid is no greater than 0.5%. The nanofluid’s viscosity increases with increasing MXene concentration but decreases with temperature. However, the value is still low with no more than 7.4 mPa·s. An optimization study reveals that the optimal MXene concentration is 0.1664 mass% for maximizing the nanofluid heat transfer efficiency. Application in a PV/T system demonstrated that the nanofluid improves overall system efficiency by enhancing thermal and electrical efficiencies and reducing the PV module surface temperature. As the Reynolds number increases from 200 to 700, the heat transfer rate increases, but the Prandtl number decreases. A figure of merit, which compares increase in the heat transfer with the corresponding pumping power, gives the overall effectiveness of the nanofluid in the system. The value ranges from 0.8 to 2.1, where the higher value signifies a better advantage. The results suggest that the aqueous inhibited propylene glycol/MXene nanofluid is a promising candidate for advanced cooling solutions in photovoltaic/thermal systems.